Oxidation of Elemental Sulfur in Granular Fertilizers Depends on the Soil‐Exposed Surface Area. Issue 2 (2nd March 2016) - Degryse, Fien; Ajiboye, Babasola; Baird, Roslyn; da Silva, Rodrigo C.; McLaughlin, Mike J.
Abstract : Core Ideas: Judicious use of elemental S fertilizers requires knowledge of their oxidation rate. Little is known about the oxidation rate of commercial granular ES fertilizers. The oxidation rate of granular fertilizers was determined. Oxidation was four times slower for ES‐fortified N–P fertilizer than for powdered ES. Oxidation was 30 times slower for ES pastilles than for powdered ES. Elemental S (ES) is the most concentrated S source and does not leach readily in soils but only becomes available to plants after oxidation to SO4 –S. Commercial ES fertilizers are usually in granular form (e.g., as ES prills or ES‐fortified N–P–K fertilizer), but studies on ES oxidation have mostly focused on ES powder mixed through soil. We studied the oxidation of commercial granular ES fertilizers and powdered ES in a column incubation experiment at 25°C with three soils (two Mollisols and an Oxisol). The columns were leached at periodic intervals, and ES oxidation was evaluated by measuring S in the leachates and by analyzing ES remaining in the soil at the end of the experiment (56 or 36 wk). Sulfate immobilization in organic matter was taken into account in the derivation of the ES oxidation rate. For all three soils, the oxidation rate was around 0.02 d −1 for ES particles (diameter <100 μm) mixed with soil, around 0.005 d −1 for ES‐fortified monoammonium phosphate granules with up to 7.5% (<100 μm) ES, and around 0.0006 d −1 for ES–bentonite pastilles (90% ES). The slower oxidation of granular than of powdered ES was attributed to the reduced surface area in contact with the soil. Knowledge of the oxidation rate of fertilizer ES is important for improving fertilizer management. This study shows that the oxidation rate of granular ES fertilizers differs greatly depending on their composition and provides the first quantitative assessment of the oxidation rate of ES in S‐fortified N–P fertilizers.